Exploring ethical practice in NGOS on mental health research in Malawi. - Action Amos; Cristobal Guerra; Corinne Reid; Edgardo Toro; Clara Calia (PLOS Global Public Health)
In recent years, an increasing trend in mental health research has been to collaborate with non-governmental organizations [NGOs] and their constituents. However, ethical difficulties can arise as a result of such partnerships. Understanding the ethics-related practices of NGOs engaged in mental health research is therefore critical. This study addressed these questions in a Malawian context. The goal of this study was to investigate NGO's ethical practices in relation to mental health research by identifying characteristics that influence ethical practices and investigating staff conceptualization of ethics and mental health. Twenty individuals who work for different local NGOs took part in one-on-one interviews or a workshop about their engagement in diverse research initiatives. They pinpointed the areas that needed improvement, as well as the challenges and chances to create partnerships and increase research capability. The diversity in conceptualizing mental health was a key influence on research practices, with heterogeneity in definitions reflected in the use of cultural, spiritual, behavioural, or medical terms. Notably, there was also a greater emphasis on procedural ethics than ethics-in-practice. Collaboration dynamics and limited staffing capacity were cited as major ethical practice considerations. Each of these elements have an impact on NGOs' ethical behaviour when conducting mental health research. Participants in the study saw engagement with notions of both ethics and mental health as lacking or rudimentary in their institutions and felt that they needed to be improved through capacity building and stronger research involvement.